TANGGUNG JAWAB RUMAH SAKIT UMUM DAERAH BANGKINANG TERHADAP KESELAMATAN PASIEN TERKAIT PELAYANAN RUMAH SAKIT DALAM KEADAAN DARURAT BERDASARKAN UNDANG-UNDANG NOMOR 44 TAHUN 2009 TENTANG RUMAH SAKIT - Fuad Muhammad Abdul Salam Rasyad; Rika Lestari; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Health care is the right all Indonesian citizens. Health care is crucial and should be maintained or improved its quality in accordance to applicable service standards without prejudice to the rights of patients, therefore the patient can feel a safe, qualified, and anti-discrimination health care. Hospital as a means of health service delivery is the spearhead of health development in Indonesia. In fact, there has been a social malfunction of hospitals, which is turned into seeking benefits for certain parties that ignore the rights of patients to receive appropriate services. According to the Law No. 44 Year 2009 on Hospital described that hospital has legal responsibility for all losses incurred on omissions by medical staff in the hospital. The Regional General Hospital (RSUD) of Bangkinang perform their duties according to the Standard Operating Procedures (SOP) and Regulation Legislation. The hospital has an obligation under Section 29 Numbers 1 of Law No. 44 Year 2009 regarding Hospitals and preserve the rights of patients as a hospital responsibility in conducting their duties of health care.The issues and goals discussed in this thesis are to determine how is the responsibilities of the regional general hospital of Bangkinang for the patient safety related to the hospital services in emergencies based on Law Number 44 Year 2009 on Hospitals and what are the barriers to The Regional General Hospital Bangkinang in the hospital service in case of emergency. The study was conducted at The Regional General Hospital of Bangkinang in Kampar regency. The samples taken in this study was 109 people. This study was used a descriptive sociological research. The data were obtained by primary and secondary data. Data collection techniques were interview, questionnaire, and literature review. Then analyzed by qualitative descriptive analysis.The result showed that the patient as health care recipient could claim for the damages which refers to Law No. 44 Year 2009 on Hospital, when health care by the hospital irrelevant and harmful to the patient. Hospitals as health care providers have a responsibility in providing services according to the Article 29 of Law Number 44 Year 2009 About Hospital. The problems occured in The Regional General Hospital of Bangkinang were caused by the hospital and patients due to minimum application of law and lack of knowledge dissemination to the public about the legislation.It can be suggested for Local Government and Hospital to create some policies on the granting of dissemination to the public about the legislation, therefore the patients will be more understand in meaning between the hospital and the community. The hospital also had to optimize their performance in health care and to equip all of supporting services.Keywords: Responsibility – Hospital - Health – Patients